Non-euro countries in the EU after Brexit: Between fear of losing of political influence and Euro accession - Paweł Tokarski; Serafina Funk (Stiftung Wissenschaft und Politik (SWP), 2019)
Despite the United Kingdom never having adopted the euro, the upcoming Brexit will have consequences not only for the European Union as a whole but also for monetary integration. The UK's withdrawal from the EU will heighten fears among the 'euro-outs', the eight Member States that have not adopted the euro, that their influence over the Union's decision-making processes will diminish in the future. Their concern has led to the formation of a new coalition of states uniting the interests of the northern euro members and some countries outside the eurozone. Although the debate over enlarging the eurozone is now subsiding, the 'Brexit moment' could trigger a new dynamic and act as a driver for expanding the eurozone or strengthening some non-euro states' links to the banking union.
Keywords: 320